Optimization of Hydraulic Pump Unit Control Communication with Seven Tools Method to Reduce Raw Mill Downtime In PT. Semen Gresik - Fauzan, Zulfahmi; Indriastiningsih, Erna; Primasanti, Yunita; Nugrahadi, Bekti (Institut Teknologi Bisnis AAS Indonesia, 2025)
The Indonesian cement industry faces challenges in improving operational efficiency amid increasing competition. One critical factor in cement production is the operational stability of the Raw Mill, which depends on the performance of the Hydraulic Pump Unit. This study aims to optimize control communication in the Hydraulic Pump Unit to reduce downtime in the Raw Mill area of PT. Semen Gresik. Using the Seven Tools method, the study identified communication disruptions as the primary cause of downtime. Key issues include unreliable remote I/O PLCs, high operating temperatures, excessive loops, poor grounding, and procedural errors. To address these problems, the study proposes replacing remote I/O PLCs, adding Junction Boxes, relocating PLCs to a control panel room, redesigning the network topology, switching from Ethernet to Profibus, improving grounding, conducting training, and updating maintenance standards. The implementation of these solutions successfully reduced Raw Mill downtime, improved production efficiency, and enhanced control system reliability by creating new operational standards. These findings highlight the importance of effective control communication in maintaining stable and efficient cement production operations.